Culture Medium Enriched with Ultrafine Carbon Monoxide Bubbles Enhances In Vitro Blastocyst Formation of In Vivo-Fertilized Mouse Zygotes - Toyofumi Hirakawa; Kazuhiko Nakabayashi; Noriko Ito; Keisuke Ishiwata; Daichi Urushiyama; Kohei Miyata; Tsukasa Baba; Kenichiro Hata; Shin’ichiro Yasunaga; Fusanori Yotsumoto; Katsuro Tachibana; Shingo Miyamoto (Antioxidants, 2025)
Oxidative stress induced by in vitro culture conditions impedes the differentiation of fertilized zygotes. Gasotransmitters containing carbon monoxide (CO) exhibit antioxidant properties when exogenously administered at appropriate concentrations. In this study, CO was incorporated into ultrafine bubbles (UFBs) to devise an innovative method for promoting the efficient differentiation of fertilized mouse zygotes into blastocysts within an in vitro culture environment. While CO typically dissipates rapidly in culture media, its encapsulation into UFBs enabled its prolonged retention within the medium. Fertilized mouse zygotes cultured in the UFB medium exhibited a significantly higher rate of blastocyst hatching compared to those cultured in conventional media. Furthermore, Gene Ontology analysis revealed elevated expression of mitochondrial-related genes and genes essential for blastocyst maturation in the UFB culture medium. These findings underscore the potential of CO-UFB as a potent agent for improving in vitro blastocyst formation and hatching by mitigating oxidative stress, thereby offering a promising strategy for enhancing assisted reproductive technologies.